2004
DOI: 10.1002/pros.20201
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxic effects of imatinib in combination with anticancer drugs in human prostate cancer cell lines

Abstract: The simultaneous exposure of imatinib and EMP would be effective against hormone sensitive and hormone insensitive cell lines and this combination should be evaluated in clinical trials. In contrast, the simultaneous exposure of imatinib and docetaxel would have little therapeutic efficacy. Although there are gaps between in vitro studies and clinical trials, the present findings provide useful information for the establishment of clinical protocols involving imatinib in hormone-refractory prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…When we compared the cytotoxic activity of Teucrium persicum with that of some known anti-cancer drugs, we found that the IC 50 value of Teucrium persicum extract for PC-3 cells was much lower. The IC 50 values reported for doxorubicin, imatinib and etoposide against PC-3 cells are 500, 5700 and 1730 μg/ml respectively (Kubler et al, 2005;Dudley et al, 2008;Tsakalozou et al, 2012) which are much higher than that of Teucrium persicum extract (142μg/ml).…”
Section: Discussionmentioning
confidence: 76%
“…When we compared the cytotoxic activity of Teucrium persicum with that of some known anti-cancer drugs, we found that the IC 50 value of Teucrium persicum extract for PC-3 cells was much lower. The IC 50 values reported for doxorubicin, imatinib and etoposide against PC-3 cells are 500, 5700 and 1730 μg/ml respectively (Kubler et al, 2005;Dudley et al, 2008;Tsakalozou et al, 2012) which are much higher than that of Teucrium persicum extract (142μg/ml).…”
Section: Discussionmentioning
confidence: 76%
“…Our data suggest a strong association between imatinib therapy and systemic p-PDGFR inhibition consistent with the known effect of the drug but we found that for the study population as a whole, increasing p-PDGFR inhibition was associated with a diminished probability of a PSA decline by 50% and a trend toward shorter PFS. These findings are of concern in light of a report that imatinib had antagonistic effects against docetaxel in PC3 cells (30). Although we have been unable to duplicate such in vitro findings, the implications of our experimental results may require further scrutiny in studies involving PDGFR inhibitors combined with taxanes in other neoplasms (7,8).…”
Section: Discussionmentioning
confidence: 80%
“…In vitro studies showed that the IC 50 of imatinib on PDGFR highly expressed tumor cell lines, such as prostate, ovarian, and cervical cancer, was in the 10-15 µM range, which is far higher than the plasma concentration arising from the usual imatinib dose of 400 mg/day. 9,[15][16][17] Furthermore, nonspecific drug binding in the plasma, particularly alpha-1-acid glycoprotein (AGP) binding can decrease the free, and therefore active, concentration of the drug, and hence reduce the tumor cellular concentration of imatinib. 18 Therefore, considering the referred nonspecific drug binding with AGP and the fact that the allowed imatinib dose cannot reach the effective cancer cellular concentration, we hypothesized that loading of imatinib in a drug delivery system would be a promising therapeutic approach in cervical cancer.…”
Section: Introductionmentioning
confidence: 99%